Family related adverse childhood experiences as risk factors for psychiatric disorders in Nigeria (2010)
"Adverse childhood experiences have been associated with a variety of mental health problems in adult life. Aims To examine whether this reported link between childhood experiences and mental health disorders in adult life applies in a Sub-Saharan African setting where cultural and family attributes may be different. Method A multistage random sampling was used in the Nigerian Survey of Mental Health and Well-Being (NSMHW) to select respondents for face-to-face interviews. Assessments of family-related adverse childhood experiences and lifetime mental health disorders were conducted with the Composite International Diagnostic Interview (CIDI 3.0). Results Almost half of the respondents had experienced an adverse childhood experience within the context of the family before they were 16 years of age. Associations between adverse childhood experiences and adult mental health disorders were few and were attenuated when clustering of adverse childhood experience and disorder comorbidities were accounted for. There was an elevated likelihood of adult substance use disorders among individuals who had experienced family violence and neglect or abuse. Parental psychopathology was associated with a significantly increased risk for developing mood disorders. Conclusions Adverse childhood experiences reflecting violence in the family, parental criminality and parental mental illness and substance misuse were more likely to have significant mental health consequences in adulthood"